Curb parking in Campus and Stimulating Students to use Public Bus within National University of Malaysia (UKM) Campus - Alaa A. Shakir; Ali Ahmed Mohammed (International Journal of Advances in Applied Sciences, 2013)
Given the great demand for parking and the implications in the environmental of commuting, universities not in the national university of Malaysia (UKM) only but around the world are implementing strategies to reduce dependence on private vehicles and increase the use of alternative modes of transport. That it must be that the system provides transportation comfort, save the time and be a friend of the environment. Were distributed in n= 80 samples for a survey of students to know the behavior of the student for transportation provided on campus. Noted in the questionnaire that focused on graduate students because they represent the largest proportion. In this questionnaire was to know about student behavior and prevent parking on campus and what is reason that prevents students from turning to public transport within the campus. The results shows that 65% use own vehicle and 35 % use public bus which shows the size of problem.